2009
DOI: 10.1093/jac/dkp367
|View full text |Cite
|
Sign up to set email alerts
|

Non-compliance with recommendations for the practice of antibiotic prophylaxis and risk of surgical site infection: results of a multilevel analysis from the INCISO Surveillance Network

Abstract: A too-short SAP duration was the most important SAP malpractice associated with an increased risk of SSI. Information directed at practitioners should be reinforced based on standard recommendations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
64
7
10

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(91 citation statements)
references
References 30 publications
10
64
7
10
Order By: Relevance
“…Studies conducted in Asian countries have generally reported higher prevalence of inappropriate antibiotic use for prophylaxis (48-100%) when compared to developed countries (23.4%-55.2%) [15,16,17,18,19]. Inappropriate timing of antibiotic administration (36.4%) and inappropriate duration (34.5%) were found to be the main reasons for inappropriate prophylactic antibiotic which was also similar to previous studies [17,18,20]. The inappropriate timing of administration in our setting was most likely due to the lack of local institutional guidelines.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies conducted in Asian countries have generally reported higher prevalence of inappropriate antibiotic use for prophylaxis (48-100%) when compared to developed countries (23.4%-55.2%) [15,16,17,18,19]. Inappropriate timing of antibiotic administration (36.4%) and inappropriate duration (34.5%) were found to be the main reasons for inappropriate prophylactic antibiotic which was also similar to previous studies [17,18,20]. The inappropriate timing of administration in our setting was most likely due to the lack of local institutional guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…The 16 (19.3%) courses of antibiotics given post-operatively may reflect a practice that could be easily targeted for intervention. Unnecessarily prolonging the duration of prophylaxis does not necessarily lead to better outcomes, but instead predisposes to selective pressure for resistant bacteria [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 The compliance to these recommendations was low in both time periods. Although the rate is comparable with other published data, 15 measures should be implemented to improve adequate redosing.…”
Section: Discussionmentioning
confidence: 96%
“…Lack of necessary prophylactic redosing has been reported as a significant risk factor for SSI in various surgical fields (19,25), while continuing prophylaxis for more than 24 hours postoperatively was found to be of no additional protective benefit (10,17,18). Some studies showed prolonged antibiotic prophylaxis was correlated with an increased risk of acquired antibiotic resistance (10, 11).…”
Section: Discussionmentioning
confidence: 99%